Opportunities or new disadvantages? The long-term impact of curriculum modifications and accommodations on post-compulsory educational trajectories - Lustenberger, Sara; Sahli Lozano, Caroline; Brandenberg, Kathrin; Hauser, Janine; Wüthrich, Sergej (Empirical Research in Vocational Education and Training, 2025)
This study examines the long-term effects of two different integrative school measures in lower secondary education — reduced individual learning objectives and accommodations — on post-compulsory educational trajectories in Switzerland. Based on data from the Bernese Longitudinal Study on Integrative School Measures (BELIMA; N = 2297), this study examines how these measures influence students’ transitions to upper secondary education, focusing on the level of academic demands and educational discontinuities (delayed entry and apprenticeship contract terminations). Through propensity score matching, students with and without integrative measures were compared while controlling for various factors including school type, academic performance, intelligence, and social background. Results show that students with reduced learning objectives were significantly more likely to enrol in educational programs with lower academic demands compared to similar students without this measure. However, they did not experience more discontinuous pathways. No effects were found for students with accommodations, neither regarding the level of academic demands nor educational discontinuities. These findings suggest that reduced learning objectives may limit educational opportunities beyond compulsory education, potentially due to their stigmatizing effects. This raises important questions about how integrative measures can be implemented to support students effectively while avoiding unintended negative consequences for their educational trajectories.